2009
DOI: 10.3386/w15158
|View full text |Cite
|
Sign up to set email alerts
|

The 2007 Subprime Market Crisis Through the Lens of European Central Bank Auctions for Short-Term Funds

Abstract: In this paper we study European banks' demand for short-term funds (liquidity) during the summer 2007 subprime market crisis. We use bidding data from the European Central Bank's auctions for one-week loans, their main channel of monetary policy implementation. Through a model of bidding, we show that banks' behavior reflects their cost of obtaining short-term funds elsewhere (i.e., in the interbank market) as well as a strategic response to other bidders. We find considerable heterogeneity across banks in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
108
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(122 citation statements)
references
References 38 publications
13
108
1
Order By: Relevance
“…24 We believe that this model is more realistic than a complete information model because students are unlikely to be aware of all the reports that will be submitted by others. This assumption is commonly made in the analysis of other non-dominant strategy mechanisms, for example, in empirical analysis of auctions (Guerre et al, 2000;Cassola et al, 2013, among others).…”
Section: Rational Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 We believe that this model is more realistic than a complete information model because students are unlikely to be aware of all the reports that will be submitted by others. This assumption is commonly made in the analysis of other non-dominant strategy mechanisms, for example, in empirical analysis of auctions (Guerre et al, 2000;Cassola et al, 2013, among others).…”
Section: Rational Expectationsmentioning
confidence: 99%
“…The proposed two-step estimator uses insights from the industrial organization literature, specifically the estimation of empirical auctions (Guerre et al, 2000;Cassola et al, 2013), single agent dynamic models (Hotz and Miller, 1993;Hotz et al, 1994), and dynamic games (Bajari et al, 2007;Pakes et al, 2007;Aguirregabiria and Mira, 2007). As in the methods used in those contexts, we use a two-step estimation procedure where the distribution of actions from other agents is used in a first step estimator.…”
Section: Related Literaturementioning
confidence: 99%
“…They do not focus on the response of the overnight rate to auction outcomes. The second group of papers explores banks' bidding behavior in central bank auctions, see e. g. Linzert et al (2007), Bindseil et al (2009), andCassola et al (2009). Using individual bidding data, it can be shown that money market conditions significantly affect banks' bidding behavior.…”
Section: List Of Tablesmentioning
confidence: 99%
“…in order to make sure that they receive at least a minimum level of liquidity, see e.g. Cassola et al (2009). Finally, according to Välimäki (2008), banks may also bid at higher rates because they are uncertain about the auction's marginal rate.…”
Section: The Response Of Money Market Rates To Mro Auction Outcomes 3mentioning
confidence: 99%
“…Bindseil et al (2009) and Cassola et al (2013) …nd that the heterogeneity of bidders in liquidity auctions is relevant. Cassola et al (2013) analyze the evolution of bidding data from the European Central Bank's weekly re…nancing operations before and during the early part of the …nancial crisis.…”
mentioning
confidence: 99%